Detection of fault and load increase for distance relay operation using FFT: article / Nor Massita Sukirman - Sukirman, Nor Massita (2013)
Undesirable operation of distance relays is due to occurrence of load increase but not because of fault. That operation has contributed to voltage collapses worldwide and it has played a part in many major blackouts. This problem occurred because of distance relay failed to differentiate between fault occurrence and load increase in power distribution system. This research presents a new approach to improve the identification of fault occurrence and load increase to prevent distance relay mal-operation. The main objective of this research presented in this thesis is basically focuses on how to differentiate between fault occurrence and load increase in transmission lines.